2020
DOI: 10.3390/cryst10121092
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Study on the High-Performance p++-GaAs/n++-GaAs Tunnel Junctions with Silicon and Tellurium Co-Doped InGaAs Quantum Well Inserted

Abstract: The development of high-performance tunnel junctions is critical for achieving high efficiency in multi-junction solar cells (MJSC) that can operate at high concentrations. We investigate silicon and tellurium co-doping of InGaAs quantum well inserts in p++-GaAs/n++-GaAs tunnel junctions and report a peak current density as high as 5839 A cm−2 with a series resistance of 5.86 × 10−5 Ω cm2. In addition, we discuss how device performance is affected by the growth temperature, thickness, and V/III ratio in the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The Al-rich barrier layer limits the out-diffusion of dopants from the TJ to other layers of the semiconductor structure and preserves its electrical properties even after annealing and/or high-temperature growth of subsequent layers . Another promising way to improve the electrical performance of high-bandgap TJ is to insert a quantum well (QW) in the p–n interface which will result in band bending due to the band offset that shortens the tunneling distance. , …”
Section: Introductionmentioning
confidence: 99%
“…The Al-rich barrier layer limits the out-diffusion of dopants from the TJ to other layers of the semiconductor structure and preserves its electrical properties even after annealing and/or high-temperature growth of subsequent layers . Another promising way to improve the electrical performance of high-bandgap TJ is to insert a quantum well (QW) in the p–n interface which will result in band bending due to the band offset that shortens the tunneling distance. , …”
Section: Introductionmentioning
confidence: 99%
“…Gou et al reported experimental and modelling studies of a series of highperformance inorganic semiconductor devices based on doped GaAs and related materials [25].…”
mentioning
confidence: 99%